KREATIVITAS GURU MUDA EDUPRENUR DALAM MENGEMBANGKAN BIMBINGAN BELAJAR BERBASIS TEKNOLOGI DI LINGKUNGAN PEDESAAN - Tia Meisaroh; Rahma Aulia Irmiati; Amelia Gita Maharani; Muhammad Zufar Sabiq; Harits Mafaza Ahsan; Ferida Rahmawati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
Advances in digital technology have led to innovations in learning and business opportunities in education (edupreneurship). In rural areas, limited facilities, access to technology, and economic conditions pose challenges to the development of tutoring. This study aims to describe the creativity of young teachers in developing technology-based tutoring as a form of edupreneurship in rural areas. The research used a descriptive qualitative method with data collection techniques through in-depth interviews, observation, and documentation of a young teacher who manages tutoring. The results showed that teachers utilized simple technologies such as Canva, Pinterest, Kahoot, Spinwheel, and Google-based educational games to increase students’ interest and understanding of learning. A warm interpersonal approach also created a comfortable and motivating learning atmosphere. The main challenges include the limited number of tutors, students’ dependence on a single teacher, and the economic conditions of the community. The study concludes that creativity, the use of technology, and the interpersonal skills of teachers are key factors in the success of edupreneurship-based tutoring in rural areas.